A new monotypic genus and new species of lady beetle (Coleoptera: Coccinellidae: Coccinellini) from western South America - Vandenberg, Natalia J. (Zootaxa, 2019)
A new monotypic genus Argosadalia gen. nov. and new species A. priscilla sp. nov. are described from the forests of Bolivia, Ecuador, and Peru. The new taxon is placed in the tribe Coccinellini in a group informally designated as the “Neda-group,” and comprising the genera Neda Mulsant; Mononeda Crotch; Neoharmonia Crotch and Argosadalia. Key morphological and anatomical characters of the new taxa are described and illustrated and the character states that define the Neda-group are reviewed.